2012
DOI: 10.14448/jes.02.0005
|View full text |Cite
|
Sign up to set email alerts
|

The Role of the Environmental Manager in Advancing Environmental Sustainability and Social Responsibility in the Organization

Abstract: A changing business climate has led many organizations to embrace environmental sustainability and social responsibility; however, organizational roles and responsibilities in sustainability initiatives have not been clearly defined. This paper specifically examines the role of environmental managers in advancing environmental sustainability and social responsibility. It is part of a broader study to identify the extent to which various departments or functional units within an organization are prepared to pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 9 publications
0
18
0
Order By: Relevance
“…There is rich literature associating environmental leadership with various organizational environmental benefits. The survey of Greenwood et al (2012) showed that environmental managers play a key role in promoting sustainable development of organizations. Dubey et al (2015) found that environmental leadership positively influences organizations' overall quality management and supplier relationship management, thereby improving the organization's environmental performance.…”
Section: Environmental Leadership and Firm Performancementioning
confidence: 99%
“…There is rich literature associating environmental leadership with various organizational environmental benefits. The survey of Greenwood et al (2012) showed that environmental managers play a key role in promoting sustainable development of organizations. Dubey et al (2015) found that environmental leadership positively influences organizations' overall quality management and supplier relationship management, thereby improving the organization's environmental performance.…”
Section: Environmental Leadership and Firm Performancementioning
confidence: 99%
“…Within organisations, the sustainability officer and manager is involved in the “midwifery” of distributing sustainability knowledge (Yusuf 2008, p. 1170). However, despite their role and expertise, they are not often consulted in research and might be under-recognised in general (Greenwood et al , 2012). As such, we view sustainability officers and managers as a potentially rich source of information and knowledge on how HEIs develop and characterise campus sustainability.…”
Section: Sustainability Officers and Managers As Organisational Intermediariesmentioning
confidence: 99%
“…Environment, economic, and social well-being are three traditional pillars of sustainability required to gain sustainable development. There must be an equilibrium to achieve sustainability [4,6].…”
Section: Sustainability and Sustainable Developmentmentioning
confidence: 99%